2019
DOI: 10.3389/fphar.2019.01421
|View full text |Cite
|
Sign up to set email alerts
|

Dermaseptins, Multifunctional Antimicrobial Peptides: A Review of Their Pharmacology, Effectivity, Mechanism of Action, and Possible Future Directions

Abstract: Dermaseptins are a group of α-helical shaped polycationic peptides isolated from the Hylid frogs, with antimicrobial effects against bacteria, parasites, protozoa, viruses in vitro. Besides, anti-tumor effects have been demonstrated. However, few animal experiments and no clinical trials have been conducted thus far. This review summarizes the current knowledge on the pharmacology, ethno pharmacology, effectivity against infectious pathogens and tumors cells and the mechanism of action of the Dermaseptins. Fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 110 publications
0
65
0
Order By: Relevance
“…In the bottom left corner of the figure, we observed several amphibian dermaseptins (e.g. APD00162, APD00163, APD00942, APD00943, APD00963, APD01351, APD01352-lime green circles) and a pair of piscine hepcidicins (APD01701, APD01702-forest green circles), none of these peptides were tested against human erythrocytes 57,58 . Besides, miscellaneous AMPs from that cluster, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In the bottom left corner of the figure, we observed several amphibian dermaseptins (e.g. APD00162, APD00163, APD00942, APD00943, APD00963, APD01351, APD01352-lime green circles) and a pair of piscine hepcidicins (APD01701, APD01702-forest green circles), none of these peptides were tested against human erythrocytes 57,58 . Besides, miscellaneous AMPs from that cluster, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Dermaseptins (DRS) are polycationic peptides isolated from Phyllomedusa frogs that are effective against bacteria, parasites, protozoa, viruses, and cancer cells in vitro. The antimicrobial and anti-cancer activity involves the destruction of cell membranes through a carpet-like model based on their binding to the outer phospholipid layer which causes the pores formation and internalization between the phospholipid heads [ 106 ]. Dos Santos et al reported that dermaseptin B2 (DRS-B2) appears to be active towards the sulphated glycosaminoglycans (GAGs) present on the surface of PC3 prostate cancer cells membranes [ 107 ].…”
Section: Critical Issues Possible Solutions For Clinical Use Of Amentioning
confidence: 99%
“…Such interactions may cause greater fluidity of tumor cell surfaces and increased destabilization thus influencing the receptors link and communications between the environment and the tumor cells [ 36 ]. DRS-B1-B2, DRS-S1-S5 DRS-O1, DRS-CA1 DRS-DU1 are effective against fungi in vitro demonstrating cytotoxicity on Candida albicans cultures, with DRS-S3 triggering apopotosis [ 106 ]. The DRS-S4 and DRS-9 possess antiviral activities against HPVs, associated with genital infection and cancer, and HSV by interfering with viral and cellular factors in the early phase of viral replication.…”
Section: Critical Issues Possible Solutions For Clinical Use Of Amentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobial peptides (AMPs) are a special class of biologically active peptides [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. They are important because of their antimicrobial effects on various pathogens, including drug-resistant bacteria, fungi, viruses, and parasites.…”
Section: Introductionmentioning
confidence: 99%